Effect of Decellularized Extracellular Matrix Bioscaffolds Derived from Fibroblasts on Skin Wound Healing and Remodeling - Kim, Hyo-Sung; Hwang, Hyun-Jeong; Kim, Han-Jun; Choi, Yeji; Lee, Daehyung; Jung, Hong-Hee; Do, Sun Hee (Frontiers in Bioengineering and Biotechnology, 2022)
The mammalian tissue extracellular matrix (ECM) has been used as a scaffold to facilitate the repair and reconstruction of numerous tissues. However, material properties of decellularized ECM (dECM) from in vitro cell cultures and the effect of these properties on wound remodeling remain unclear. To elucidate its biological activity, we extracted ECM from human lung fibroblasts, fabricated it into a patch, and applied it to a full-thickness skin wound. The fibroblast-derived extracellular matrix (fdECM) maintained the content of collagen Ⅰ, collagen Ⅳ, and elastin, and the extraction process did not damage its critical growth factors. The fdECM-conjugated collagen patch (COL-fdECM) facilitated wound contraction and angiogenesis in the proliferative phase when applied to the in vivo full-thickness skin wound model. Moreover, the COL-fdECM treated wound showed increased regeneration of the epidermal barrier function, mature collagen, hair follicle, and subepidermal nerve plexus, suggesting qualitative skin remodeling. This therapeutic efficacy was also similarly observed when applied to the diabetic ulcer model. fdECM was shown to help remodel the tissue by regulating FGFs, MMPs, and TIMPs via the p38 and ERK signaling pathways in an in vitro experiment for understanding the underlying mechanism. These results provide a biological basis for cell-derived ECM as a multi-functional biomaterial applicable to various diseases.